Results from 10 Years of a CBT Pain Self-Management Outpatient Program for Complex Chronic Conditions. (6th November 2016) - Boschen, Kathryn A.; Robinson, Edward; Campbell, Kent A.; Muir, Sarah; Oey, Elvina; Janes, Kristen; Fashler, Samantha R.; Katz, Joel
Abstract : Background. Traditional unimodal interventions may be insufficient for treating complex pain, as they do not address cognitive and behavioural contributors to pain. Cognitive Behavioural Therapy (CBT) and physical exercise (PE) are empirically supported treatments that can reduce pain and improve quality of life. Objectives. To examine the outcomes of a pain self-management outpatient program based on CBT and PE at a rehabilitation hospital in Toronto, Ontario. Methods. The pain management group (PMG) consisted of 20 sessions over 10 weeks. The intervention consisted of four components: education, cognitive behavioural skills, exercise, and self-management strategies. Outcome measures included the sensory, affective, and intensity of pain experience, depression, anxiety, pain disability, active and passive coping style, and general health functioning. Results. From 2002 to 2011, 36 PMGs were run. In total, 311 patients entered the program and 214 completed it. Paired t -tests showed significant pre- to posttreatment improvements in all outcomes measured. Patient outcomes did not differ according to the number or type of diagnoses. Both before and after treatment, women reported more active coping than men. Discussion. The PMGs improved pain self-management for patients with complex pain. Future research should use a randomized controlled design to better understand the outcomes of PMGs.